Housing as a social determinant of health: System perspectives from lived experience, policy and evidence - Lisa Garnham; Katherine Smith; Ellen Stewart; Clementine Hill O'Connor (Journal of Critical Public Health)
Poor housing is a recognised contributor to poor health but, like many ‘wicked’ issues, policy intervention has proved challenging. This paper considers efforts to use systems mapping, a core systems science tool, to support housing policy teams in northern England to identify housing policy options to improve health. We compare housing-health systems maps created from three perspectives: (1) research evidence; (2) policymakers; and (3) people with lived experience. Employing Bevir & Rhodes’ 3Rs framework (ruling, rationalities and resistance), our analysis finds significant alignment between (1) and (2), reflecting an alignment between ‘ruling’ and ‘rational’ perspectives that is associated with efforts to achieve evidence-based policy. By contrast, lived experience accounts ‘resisted’ aspects of the policy and evidence-led maps, and offered markedly different insights. While all three maps reflected the four ‘pillars’ of housing (cost, condition, context and consistency), the maps created by people with lived experience underline the importance of people’s sense of ‘control’. We reflect on the need to decentre dominant ‘evidence cultures’ in policy and public health, concluding that, if systems science is to deliver on the promise of helping tackle ‘wicked’ policy issues, further innovation is needed, incorporating experiential evidence in ways that help address the unequal power dynamics at play.